Prognostic impact of pleural lavage cytology in patients with primary lung cancer. (December 2016) - Tomizawa, Kenji; Nishino, Masaya; Sesumi, Yuichi; Kobayashi, Yoshihisa; Sato, Katsuaki; Chiba, Masato; Shimoji, Masaki; Suda, Kenichi; Shimizu, Shigeki; Sato, Takao; Takemoto, Toshiki; Mitsudomi, Tetsuya
Highlights: Positive pleural lavage cytology (PLC+) is a negative prognostic factor in NSCLC. PLC status does not change the stage of TNM classification for lung cancer. Thirty-eight of the 754 patients were positive for PLC (5.1%). The OS curve of patients with PLC+ overlapped with that of those with PLC- and pT3. Patients with positive PLC should be staged as pT3. Abstract: Objectives: Positive pleural lavage cytology (PLC) has been reported to have a negative prognostic impact in patients with surgically resected non-small cell lung cancer (NSCLC). However, positive PLC does not upgrade the stage according to the 7th edition of TNM classification for lung cancer. The objectives of this study were to evaluate the prognostic impact of positive PLC in patients with NSCLC and to clarify its contribution to TNM classification. Materials and methods: Seven hundred fifty-four patients who underwent surgical resection of NSCLC from January 2007 through December 2013 were retrospectively studied. PLC was performed using 50 ml of saline immediately after thoracotomy. Results: Thirty-eight of the 754 patients were positive for PLC (5.1%). The overall survival (OS) of patients with positive PLC was significantly shorter than that of those with negative PLC (P = 0.007, log-rank test). In multivariate analyses of OS, positive PLC was a significant independent prognostic factor (hazard ratio = 2.21, 95% confidence interval: 1.21–4.04, P = 0.009). The OS of patients with positive PLC was significantly shorter than that of those with negative PLC and pT1 (P < 0.0001) or negative PLC and pT2 (P < 0.0001) and almost overlapped with that of those with negative PLC and pT3 disease (P = 0.601). Conclusion: Positive PLC is an independent prognostic factor in patients with resected NSCLC. Based on our analyses, we propose that patients with positive PLC be staged as pT3.